A Case-Control Study of Female Breast Cancer Risk Factors in Mauritius - Maleika Heenaye- Mamode Khan; Jasmine Fauzee; Naushad Khan; Hudaa Neetoo; Zaynab Toorabally; Yashvinee Ahku; Ashwinee Soobhug (Middle East Journal of Cancer, 2022)
Background: Female breast cancer (FBC) is a public health issue which represents the third leading cause of deaths in Mauritius (accounting for 13.5% of all the deaths in 2017), after diabetes and cardiovascular diseases. The present research aimed to identify the potential causative factors associated with FBC in Mauritius, given the genetic polymorphisms of different ethnic groups. Method: From January to August 2019, a questionnaire was administered to women who had consented to participate in this case-control study. Overall, there were 394 women, comprising 149 cases and 245 controls. The cases were BC patients who visited two non-governmental organizations (NGOs) involved in providing support and counselling to BC patients in Mauritius. The controls were women matched by age approached from these NGOs as well as the public at large. A logistic regression model was then applied in R statistical software to identify the potential significant factors associated with BC in Mauritius. Results: Herein, age, family history of cancer, the prolonged use of female hormone as contraception, smoking habits, consumption of non-bio food products, and the frequent use of plastic bottles and Styrofoam containers to serve hot food were identified as the determinant factors attributing to BC incidence. Conclusion: The extended use of female hormones for birth controls, smoking habits, consumption of non-bio food products, along with the frequent use of plastic bottles and Styrofoam containers to serve hot food were identified as modifiable factors. There is an urgent need for sensitizing people to change their lifestyle in order to minimize their risk of developing breast cancer.